2020
DOI: 10.3390/antiox9100980
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nrf2 in Liver Diseases: Molecular, Pharmacological, and Epigenetic Aspects

Abstract: Liver diseases represent a critical health problem with 2 million deaths worldwide per year, mainly due to cirrhosis and its complications. Oxidative stress plays an important role in the development of liver diseases. In order to maintain an adequate homeostasis, there must be a balance between free radicals and antioxidant mediators. Nuclear factor erythroid 2-related factor (Nrf2) and its negative regulator Kelch-like ECH-associated protein 1 (Keap1) comprise a defense mechanism against oxidative stress dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 131 publications
(256 reference statements)
0
46
0
1
Order By: Relevance
“…ROS can disturb liver-specific cells’ functionality and, therefore, contribute to the development of liver fibrosis [ 40 ]. Several studies have indicated that the liver’s fibrotic disease process is characterized by a decrease in the functioning of the antioxidant defense system associated with Nrf2 deficiency [ 41 ]. It was shown that Nrf2 deletion promoted marked oxidative stress, inflammation, and fibrosis in mouse liver [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS can disturb liver-specific cells’ functionality and, therefore, contribute to the development of liver fibrosis [ 40 ]. Several studies have indicated that the liver’s fibrotic disease process is characterized by a decrease in the functioning of the antioxidant defense system associated with Nrf2 deficiency [ 41 ]. It was shown that Nrf2 deletion promoted marked oxidative stress, inflammation, and fibrosis in mouse liver [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is also involved in lipid metabolism and may play a role in the protection against liver damage during the development of steatosis and steatohepatitis [16]. Nrf2 is important for mitochondrial homeostasis, and it has been demonstrated that Nrf2 activation is necessary to maintain mitochondrial integrity [17] and can directly affect the efficiency of mitochondrial fatty acid oxidation [18].…”
Section: Antioxidant Balance In the Liver In Non-alcoholic Fatty Livementioning
confidence: 99%
“…Therefore, investigations of the protective effects of Keap1/Nrf2 signaling that focus on specific tissues or organs are of great interest. Such studies have traditionally focused on tissues with detoxification functions such as the liver [ 6 , 7 ] but have also expanded to diverse tissues, including the kidney [ 8 , 9 ], skin [ 10 ], lung [ 11 ], colon [ 12 ], heart [ 13 ], nervous system [ 14 ], adipose tissue [ 15 ], pancreas [ 16 ] and thyroid [ 17 , 18 ], as evidenced by the respective tissue/organ-specific studies that are outlined below and comprise the majority of studies in the present Special Issue. Lastly, research on Nrf2 has expanded to encompass not only basic but also translational and clinical studies.…”
mentioning
confidence: 99%